FDI, Regulations and Growth - Matthias Busse; José Luis Groizard Cardosa (Hamburg Institute of International Economics (HWWA), 2006)
The paper explores the linkage between income growth rates and foreign direct investment (FDI) inflows. So far the evidence is rather mixed, as no robust relationship between FDI and income growth has been established. We argue that countries need a sound business environment in the form of good government regulations to be able to benefit from FDI. Using a comprehensive data set for regulations, we test this hypothesis and find evidence that excessive regulations restrict growth through FDI only in the most regulated economies. This result holds true for different specifications of the econometric model, including instrumental variable regressions.
Keywords: C31; F43; L51; F21; 330; Multinationals; Spillovers; Institutions; Development